Effects of Gender on Electrocardiography in Subjects with Shortened Ventricular Depolarization (QRS). Issue 3 (31st August 2015) - Aydin, Fatih; Aktoz, Meryem; Altun, Armagan; Gursul, Erdal; Aksit, Ercan
Abstract : Background: Distinctions between electrocardiograms of female and male subjects have been recognized for many years. Due to these differences, arrhythmias in each gender have a tendency to differ. In our study, we aimed to compare electrocardiography intervals between men and women with short QRS durations. Methods: Subjects with a QRS interval of ≤80 ms were included in the study. Patients were grouped by gender and the parameters were compared. Patients with diseases that might affect QRS interval and/or who were on medications were excluded. The electrocardiogram intervals of the subjects were measured, Holter monitors were placed, and parameters of time‐based heart rate variation were analyzed. Results: A total of 100 patients (55% female) were included in the study. According to statistical analysis, no significant difference between the genders was observed in the heart rate or in the parameters, such as QT, JT, JTp, and TpTe intervals or heart rate‐corrected QTc, JTc, JTpc, and TpTec intervals, which affect repolarization and are known to be arrhythmia precursors by shortening or elongation. No statistically significant difference was found between the two groups for the parameters of heart rate variability time measures (SDNN, SDANN, rMSSD, and pNN50). Conclusion: We observed that when the QRS interval gets shorter, repolarization differences between the genders disappear. New studies are required on this subject.